Analysis of Muhammadiyah educational concepts: a historical and philosophical review - Jannah, Miftahul (ATTARBIYAH: Journal of Islamic Culture and Education, 2023)
Developments and problems that arise in the community are the basis for Muhammadiyah to carry out reforms. This research uses a type of literature study research. It is used to find theories related to the history and philosophy of Muhammadiyah education and is analyzed descriptively by considering ontological, epistemological, and axiological concepts in philosophy then conclusions are drawn objectively. Analysis of Muhammadiyah's educational philosophy is: first, Ontological Philosophy, which is based on the implementation and rational understanding of Islam with recognition of potential reality and facts. Second Epistemological philosophy discusses the paradigm of Muhammadiyah education on the scientific plain is to unite science with Islamic Sharia, and is displayed in an anthology that places the Qur'an and the Sunnah of the Messenger as guidelines. While on the operational plain through education Muslims are able to take part in all sectors of life and in all fields of expertise, and are in all strata of life and all strata of expertise. Third, Axiological Philosophy discusses the implementation of Muhammadiyah education carried out rationally, civilizationally, progressively or religiously scientific, which will produce generations with integrative-interconnective scientific characteristics, so that they can become Insan Kamil, namely humans with comprehensive and holistic insight.